المعجم القرآني: الحدود الفاصلة بين الكلمة والمصطلح - قروط, رضوان (جامعة الوادي - University of Eloued, 2022)
الملخص: إن المفردة القرآنية كانت محور الدرس القرآني منذ نزول القرآن، ولا تزال إلى يومنا هذا، وكان هذا التناول متمايز الأسباب، والغايات، والوسائل، والمناهج. ومن المناهج الحديثة منهج الدراسة المصطلحية لألفاظ القرآن الكريم، وموضوعها المصطلح القرآني، لكن هذا الطرح مبني على أسس معرفية لعلم المصطلح الحديث، ومن أهم هذه الأسس التفريق بين الكلمة والمصطلح، وهذا الفرق ألقى بظلاله على الدراسة المصطلحية لألفاظ القرآن الكريم؛ فهل هناك حدود حقيقية فاصلة بين الكلمة والمصطلح أم هي حدود وهمية؟ فالباحث تناول جانبا من هذه الحيثية فبدأ بالتعريف بالمعجم لغة ثم اصطلاحا؛ وهو: الرصيد الشامل لكل ما يستعمله أفراد جماعة لغوية؛ ويسمى المعجم اللساني وهو ينقسم إلى: معجم عام قوامه الألفاظ العامة (الكلمات)، ومعجم خاص وقوامه الألفاظ الخاصة (المصطلحات)، ثم من هذا المدخل فصَّل الباحث في ماهية المعجم القرآني، وتفرع البحث في مسألة تصرف الشرع في ألفاظ اللغة، وفرَّق الباحث بين العرفية العامة والعرفية الخاصة؛ وخلص في الأخير إلى أن معجم القرآن معجم عام ذو سمة عرفية ترجع إلى عرف المتكلم وما يناسبه من المعاني. Abstract: The Quranic words have been the focus of Quranic studies since the revelation of the Quran, and it continues to this day. This approach was differentiated in reasons, goals, means and methodologies . One of the modern methodologies is the terminology of the Quran, the subject of which is the Quranic terms, but this approach is based on the knowledge of modern terminology and one of these principles is the distinction between the word and the term, this distinction has actually cast a shadow on the terminological study of the Quranic words ; hence is there a real border between the word and the term or is it a phantom border? The researcher has chosen to study a specific aspect of the topic and began with the definition of lexicon based on language and terminology which are the cumulative knowledge of the members of a language group ; it's called a lexicon and it's divided into: a general lexicon consisting of general words (words) and a special lexicon with special words (phrases). From this entry, the researcher elaborated on the meaning of the Quran lexicon; Lastly, he concluded that the Quran Dictionary was a general lexicon with a customary character that was due to the knowledge of the speaker and the appropriate meaning.
Quranic lexicon: the boundaries between word and term
مقال
Keywords: المعجم القرآني ; المصطلح القرآني ; الدراسة المصطلحية; Quranic lexicon; Quranic Terms; Terminology